Microdosed cocktail of three oral factor Xa inhibitors to evaluate drug-drug interactions with potential perpetrator drugs - Mikus, Gerd; Foerster, Kathrin; Schaumäker, Marlene; Lehmann, Marie-Louise; Burhenne, Jürgen; Haefeli, Walter E. (Clinical pharmacokinetics, 2019)
OBJECTIVES: The aim of this study was to prove the suitability of simultaneously administered microdoses of the factor Xa inhibitors (FXaIs) rivaroxaban, apixaban and edoxaban (100 µg in total). To evaluate drug-drug interactions, the impact of ketoconazole, a known strong inhibitor of cytochrome P450 3A4 and P-glycoprotein, was studied. - METHODS: In a crossover clinical trial, 18 healthy volunteers were randomized to the two treatments using microdoses of rivaroxaban, apixaban and edoxaban alone and when coadministered with ketoconazole. Plasma and urine concentrations of microdosed apixaban, edoxaban and rivaroxaban were quantified using a validated ultra-performance liquid chromatography-tandem mass spectrometry assay with a lower limit of quantification of 2.5 pg/ml. - RESULTS: The microdosed FXaI cocktail showed similar pharmacokinetic parameters compared with published data, using normal therapeutic doses of each FXaI. Ketoconazole significantly increased exposure, with geometric mean AUC ratios of 1.90 (apixaban), 2.35 (edoxaban) and 2.27 (rivaroxaban). - CONCLUSION: The microdosed FXaI cocktail approach was able to precisely predict the drug interaction with ketoconazole. This is the first study that has been conducted to evaluate drug-drug interactions with a drug class, and the low administered doses also allow evaluation in vulnerable target populations. - STUDY PROTOCOL: EudraCT 2016-003024-23.